Decreased Emotional Perception in Obesity. (4th April 2016) - Giel, Katrin Elisabeth; Hartmann, Armin; Zeeck, Almut; Jux, Anna; Vuck, Alexander; Gierthmuehlen, Petra C Guess; Wetzler‐Burmeister, Edda; Sandholz, Angelika; Marjanovic, Goran; Joos, Andreas
Abstract: Background: There is hardly any empirical evidence on emotion processing by controlled studies in obesity. Material and Methods: Participants rated their emotions in response to visual emotional stimuli from the International Affective Picture System. Study 1 compared obese women with normal‐weight controls and women with eating disorders. Study 2 compared obese men with normal‐weight controls. Results: Obese women had reduced emotional intensity scores for all basic emotions and the mixed emotion sadness–fear. Obese men had reduced scores for all emotions except happiness and disgust; anger showed a trend towards significance. The results were mainly based on ratings from non‐depressed obese individuals. Discussion: Obese men and women scored significantly lower on most basic and mixed emotions. Non‐depressed obese subjects seem particularly affected. These new findings must be validated by further study, and longitudinal evaluation after weight loss, e.g. by bariatric surgery, will be of interest. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.